2021
DOI: 10.3389/fonc.2021.686308
|View full text |Cite
|
Sign up to set email alerts
|

Cemiplimab in an Elderly Frail Population of Patients With Locally Advanced or Metastatic Cutaneous Squamous Cell Carcinoma: A Single-Center Real-Life Experience From Italy

Abstract: BackgroundCutaneous squamous cell carcinoma (CSCC) is the second most common skin cancer whose incidence is growing parallel to the lengthening of the average lifespan. Cemiplimab, an antiPD-1 monoclonal antibody, is the first approved immunotherapy for patients with locally advanced CSCC (laCSCC) or metastatic CSCC (mCSCC) thanks to phase I and II studies showing high antitumor activity and good tolerability. Nevertheless, at present, very few data are available regarding cemiplimab in real-life experience an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 49 publications
(80 reference statements)
2
35
0
Order By: Relevance
“…The pooled analysis of eight studies 16–20,28–30 suggested that the overall incidence of all grade AEs was 76.9% (95% CI: 63.2%–90.7%). As for the AEs with ≥3 grades, the overall incidence was 20.2% (95% CI: 11.1%–29.3%) after meta‐analysis of eleven studies 16–22,28–31 . Further analysis indicated that pembrolizumab had better tolerability than cemiplimab.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The pooled analysis of eight studies 16–20,28–30 suggested that the overall incidence of all grade AEs was 76.9% (95% CI: 63.2%–90.7%). As for the AEs with ≥3 grades, the overall incidence was 20.2% (95% CI: 11.1%–29.3%) after meta‐analysis of eleven studies 16–22,28–31 . Further analysis indicated that pembrolizumab had better tolerability than cemiplimab.…”
Section: Resultsmentioning
confidence: 98%
“…Then, 1289 studies were excluded after initial screening of titles and abstracts. After reviewing the full text, 13 studies with 980 patients were finally included for final analysis 16–23,27–31 . Figure 1 showed the flowchart of the study screening process.…”
Section: Resultsmentioning
confidence: 99%
“…Another real-world retrospective study involving 131 patients with advanced cSCC treated with cemiplimab identified a head and neck tumor location ( p -value = 0.007) and normal haemoglobin values ( p -value = 0.034) as positive predictors; on the other hand, location on the genitalia ( p -value = 0.041), treatment with any systemic antibiotic within 1 month of cemiplimab initiation ( p -value = 0.012), performance status ≥1 ( p -value = 0.012), chronic corticosteroids therapy ( p -value = 0.038), previous radiation therapy to lymph nodes ( p -value = 0.052), and previous chemotherapy ( p -value = 0.0020) were significantly associated with a worse response [ 45 ]. In a cohort of 30 elderly frail patients with la-cSCC ( n = 25) or m-cSCC ( n = 5) treated with cemiplimab, head/neck tumor location ( p -value = 0.016) and haemoglobin > 12 g/dL ( p -value = 0.042) were similarly associated with a higher RR [ 51 ].…”
Section: Cscc and Bcc Immunobiology And Tumor-specific Predictorsmentioning
confidence: 99%
“…Absolute lymphocyte count (ALC) was investigated as a predictor of response to ICIs in the aforementioned retrospective study by Hanna et al, and a higher median ALC at therapy initiation was correlated with a good response ( p -value < 0.01) [ 179 ]. Strippoli et al also identified the association between baseline low neuthophil/lymphocyte ratio and low platelet/lymphocyte ratio as a serological predictor of better response [ 51 ]. The underlying biological hypothesis is that lymphocyte count may serve as a surrogate for estimating the number of available circulating lymphocytes that could target the tumor, thus contributing to immunosurveillance [ 179 ].…”
Section: Cscc and Bcc Immunobiology And Tumor-specific Predictorsmentioning
confidence: 99%
“…Retrospective studies have evaluated cemiplimab in aCSCC. [5][6][7][8] The common feature of the real-world series is inclusion of immunocompromised patients and higher proportion of elderly patients. Both patient cohorts achieved comparable ORR and tolerability (low discontinuation rates) to patients treated in the clinical trial and add data on a group of patients who are underrepresented in clinical trials.…”
mentioning
confidence: 99%